2020
DOI: 10.3390/app10124211
|View full text |Cite
|
Sign up to set email alerts
|

Using Low Salinity Waterflooding to Improve Oil Recovery in Naturally Fractured Reservoirs

Abstract: Low salinity waterflooding is an effective technique to accelerate and boost oil recovery. The impact of this technique has been investigated widely in laboratories for various scales and rock typing, most of which have demonstrated a potential improvement in oil recovery. This improvement has been attributed to several chemical and physical interactions that led to a change in the wettability to become more water-wet, as well as a reduction in the residual oil saturation. Meanwhile, it is rare to find a discu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…13) in the simulation model can enhance the matrix characterisation, and hence increase the simulation accuracy of low salinity waterflooding (e.g. (Aljuboori et al 2020a(Aljuboori et al , 2020b) est gratitude to Universiti Teknologi PETRONAS for providing the required software license and creating the necessary working environment. The registration fee of the conference was funded by Universiti Teknologi PETRONAS, YUTP Grant (015LC0-109).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13) in the simulation model can enhance the matrix characterisation, and hence increase the simulation accuracy of low salinity waterflooding (e.g. (Aljuboori et al 2020a(Aljuboori et al , 2020b) est gratitude to Universiti Teknologi PETRONAS for providing the required software license and creating the necessary working environment. The registration fee of the conference was funded by Universiti Teknologi PETRONAS, YUTP Grant (015LC0-109).…”
Section: Discussionmentioning
confidence: 99%
“…The matrix heterogeneity in NFR's is related to the depositional environment and the subsequent diagenesis processes that alter the depositional properties of the rocks (e.g. (Aljuboori et al 2020a)). Meanwhile, the pervasive occurring of fractures in most of the carbonate rocks creates additional heterogeneity to the system due to their multiscale and their various flow capacities (Agada et al 2013;Nelson 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it has been shown that LSWF is effective in fractured carbonates as well. 9,26,27 Nonetheless, LSWF causes fines migration and thus leads to formation damage, which could potentially reduce oil production. 28 Accordingly, NPs are injected with LSW because they possess the tendency to reduce fines migration.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the difficulties encountered during the characterization of carbonate reservoirs, the presence of fracture networks renders waterflooding techniques ineffective in most cases, which has been ascribed to the storability and permeability contrasts existing between the matrix and the fracture networks, leading to an early water breakthrough and poor sweep efficiency. Consequently, researchers have focused on the use of inexpensive and environmentally friendly EOR methods to increase oil recovery from carbonate reservoirs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation